The Correlation between Serum Level of N-Terminal Pro-B-type Natriuretic Peptide and Gensini Score in Patients with Acute Coronary Syndrome - Mohammad Hassan Namazi; Hossein Vakili; Mahsa Charkhkar; Latif Gachkar; Isa Khaheshi (International Journal of Cardiovascular Practice, 2016)
Introduction: N-terminal pro-B-type natriuretic peptide (NT-proBNP) has emerged as an important biomarker for developing the diagnosis and prognosis of cardiovascular diseases, as several studies have shown that serum levels of NT-proBNP elevate in acute coronary syndrome (ACS) and coronary artery disease (CAD). We performed this study to find any possible correlation between serum levels of NT-proBNP and Gensini score in patients diagnosed with ACS.Methods: In a cross-sectional study, 100 consecutive patients with ACS who were candidates of angiography were recruited and their serum levels of NT-proBNP, Gensini scores, lipid profiles and troponin I levels were measured.Results: Sixty six male and 34 female patients with a mean age of 57.5 years, including 44 with unstable angina, 33 with ST-elevation myocardial infarction, and 23 with non-ST-elevation myocardial infarction were enrolled. The mean serum NT-proBNP level and the Gensini score were 1987.16 pg/mL (17.9-8841) and 31.09 (6-92.5), respectively. The serum NT-proBNP levels and Gensini scores were significantly correlated with a Spearman correlation coefficient of 0.953 (P < 0.001). Serum levels of NT-proBNP were not different in patients with single-vessel disease, 2-vessel disease and 3-vessel disease (P = 0.257). NT-Pro-BNP levels were also correlated positively with troponin I levels (correlation coefficient = 0.779) and negatively with left ventricular ejection fraction (correlation coefficient = -0.55). Smoker patients had higher NT-proBNP levels (P = 0.047). Neither Gensini scores nor NT-Pro-BNP levels had significant correlation with lipid profile or blood sugar.Conclusions: NT-proBNP is directly correlated with Gensini score in patients with ACS and might be used as an important marker for risk stratification in those patients.